2016
DOI: 10.1130/g37958.1
|View full text |Cite
|
Sign up to set email alerts
|

The Thor suture zone: From subduction to intraplate basin setting

Abstract: The crustal seismic velocity structure of northwestern Europe shows a low P-wave velocity zone (LVZ) in the lower crust along the Caledonian Thor suture zone (TSZ) that cannot be easily attributed to Avalonia or Baltica plates abutting the TSZ. The LVZ appears to correspond to a hitherto unrecognized crustal segment (accretionary complex) that separates Avalonia from Baltica, explaining well the absence of Avalonia further east. Consequently, the northern boundary of Avalonia is shifted ~150 km southward. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 24 publications
5
49
0
Order By: Relevance
“…The outcome of the 3D density modelling supports previous results (Lyngsie et al, 2006;Fichler et al, 2011;Smit et al, 2016) showing that the crystalline crust of the study area is not only heterogeneous in a vertical direction but it can be also subdivided into several horizontal blocks. From the west to the east, the modelled middle crystalline crust consists of four crustal domains, two of which are represented by middle crust of Laurentia and Avalonia (layer 15) and middle crust of Baltica (layer 16) with similar densities of 2746-2761 and 2747 kg/m 3 (for the 'heavy' model 2780-2813 and 2801 kg/m 3 ), respectively (Table 3).…”
Section: Suture Zone Between Baltica Avalonia and Laurentiasupporting
confidence: 76%
See 2 more Smart Citations
“…The outcome of the 3D density modelling supports previous results (Lyngsie et al, 2006;Fichler et al, 2011;Smit et al, 2016) showing that the crystalline crust of the study area is not only heterogeneous in a vertical direction but it can be also subdivided into several horizontal blocks. From the west to the east, the modelled middle crystalline crust consists of four crustal domains, two of which are represented by middle crust of Laurentia and Avalonia (layer 15) and middle crust of Baltica (layer 16) with similar densities of 2746-2761 and 2747 kg/m 3 (for the 'heavy' model 2780-2813 and 2801 kg/m 3 ), respectively (Table 3).…”
Section: Suture Zone Between Baltica Avalonia and Laurentiasupporting
confidence: 76%
“…17C) cannot be differentiated due to the impossibility of distinguishing between the lower high-density crusts of Baltica, Laurentia and Avalonia, and a part of this layer beneath the Viking Graben may thus have at least a partial Baltican origin. On the other hand, the extension of Baltican lower crust beneath the southwestern flank of the Central Graben is not obvious according to Smit et al (2016) who suggested that there were remnants of the Caledonian accretionary complex between Avalonia and Baltica based on the presence of the low P-wave velocity zone in the lower crust of the southwestern flank of the Central Graben. The latter is reflected in part by a thinning of the high-density lower-crustal layer beneath the southwestern flank of the Central Graben in the case of our model (Figs.…”
Section: Upper-crustal Magmatic Rocksmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of the pre-Permian basement is also constrained by geophysical studies (Grad et al 2003;Dadlez et al 2005;Guterch and Grad 2010) and drill core data showing the presence of Ordovician-to-Carboniferous sediments (Podhalańska Fig. 1 a Plate tectonic sketch of West and Central Europe after Smit et al 2016; TTZ Teisseyreornquist Zone, L Laurentia; b map of northwestern Poland indicating the location of the sampling sites of PermoCarboniferous volcanic rocks. Numbers indicate the thickness of drilled volcanic rocks in meters (data from Dadlez 2006;Geiβler et al 2008).…”
Section: Introductionmentioning
confidence: 95%
“…Our data include Secondary Ion Mass Spectrometry (SIMS) U-Pb ages and O isotope analyses followed by Hf isotope analyses using Laser Ablation Inductively Coupled Mass Spectrometry (LA-ICP-MS). The goal of the present contribution is to constrain the sources of rhyolite magma in the Polish Lowlands and to fit this information into current models of continental crust and plate tectonic evolution in the region (Mazur et al 2015;Smit et al 2016;Żelaźniewicz et al 2016). In addition, we address the extent to which rhyolite magmas were the product of remelted crustal granitic bodies.…”
Section: Introductionmentioning
confidence: 99%